Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Left Hand Side :
sin
x
+
cos
x
cot
x
We know that
cot
x
=
cos
x
sin
x
Therefore
sin
x
+
cos
x
cot
x
=
sin
x
+
cos
x
⋅
(
cos
x
sin
x
)
=
sin
x
+
cos
2
x
sin
x
=
sin
2
x
+
cos
2
x
sin
x
(We know the Trigonometric Identity
sin
2
x
+
cos
2
x
=
1
)
=
1
sin
x
=
csc
x
(Because Cosecant is the reciprocal of Sine)
Hence Proved.
sin
x
+
cos
x
cot
x
We know that
cot
x
=
cos
x
sin
x
Therefore
sin
x
+
cos
x
cot
x
=
sin
x
+
cos
x
⋅
(
cos
x
sin
x
)
=
sin
x
+
cos
2
x
sin
x
=
sin
2
x
+
cos
2
x
sin
x
(We know the Trigonometric Identity
sin
2
x
+
cos
2
x
=
1
)
=
1
sin
x
=
csc
x
(Because Cosecant is the reciprocal of Sine)
Hence Proved.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.